Exploring women’s transformational leadership style and competency : a higher education Malaysia perspective / Salmiwati Othman and Aida Hanim A. Hamid - Othman, Salmiwati; A. Hamid, Aida Hanim (Universiti Teknologi MARA, 2023)
Men have traditionally held most of the top leadership positions in Malaysian higher education, notably in the country's public universities. Nevertheless, in this ever-changing world, an increasing number of empowered women are adopting leadership roles in this profession and adjusting admirably to the finest practises that will benefit the institution they represent. Seven women academic leaders at the top and middle levels were interviewed for this study to learn about their perceptions of transformational leadership and the aspects they employ to manage university personnel. Furthermore, the abilities of women academic leaders are being explored. According to the findings, women academic leaders at both levels have a clear understanding of transformational leadership, which is leadership that leads to change. Meanwhile, transformational leadership was discovered to be applied in their university leadership. When leading, informants are more likely to apply the aspects of intellectual stimulation and idealised influence. Communication and decisionmaking skills are crucial, and they should be present in every women academic leader in higher education. Women have made tremendous strides as leaders during the last decade, but they still confront several challenges. Future proposals for Malaysian higher education institutions are needed including developing relevant guidelines, a suitable model, and methodical procedures, as well as developing numerous programmes focusing on women academic leadership.